MANAGING SUSTAINABLE LIVELIHOODS ON THE EDGE: STRATEGIES FOR RURAL AND URBAN FRINGE RESILIENCE - Fauzia Afriyani (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2024)
The primary objective of this investigation is to explore and analyze sustainable livelihoods (SL) within villages situated in the RUF region. The RUF area, characterized as a transitional zone between rural and urban environments, is also referred to as suburban or hinterland. The study was specifically conducted in an RUF area proximate to Palembang, the provincial capital of South Sumatra, progressing towards Ogan Ilir Regency. The specific research locale is Pemulutan District, Ogan Ilir Regency, situated along the Palembang-Inderalaya traffic route, encompassing Pemulutan Ulu Village and Pelabuhan Dalam Village.The designated unit of analysis for this research is the Head of the Household (KK). In Pemulutan District, there are a total of 1,480 families, distributed between Pemulutan Ulu Village (691 families) and Pelabuhan Dalam Village (789 families). The sample size for Pemulutan Regency comprises 314 respondents, with 148 respondents from Pemulutan Ulu Village and 166 respondents from Pelabuhan Dalam Village.The study employs the sustainable livelihood framework, focusing on human resources as one of its key components. The findings indicate that, despite the RUF area classification, the sustainable livelihoods of residents in this region are notably suboptimal.